The Personality Of Nina Sayer In Darren Aronofsky'sBlack Swan Movie (2010): A Psychoanalytic Approach - OKTAVIANI, GARNIS (2012)
The study attempts to explore the personality of the major Character. The objective of the study is to analyze the major character based on the structural elements of the movie and psychoanalytic perspective. The researcher applies the theory of psychoanalytic proposed by Sigmund Freud. The writer conducts the research by using qualitative method that uses the library research, while the data sources are literary data that are divided into two categories, primary and secondary data. The primary data are the movie entitled Black Swan and the secondary data include several references books of Psychoanalysis. The object of the research is the movie entitled Black Swan directed by Darren Aronofsky. The results of the study are as follows. Firstly, the structural elements present a unity. It appears in the beginning, the middle, and the end of the story. Secondly, the psychoanalytic analysis shows that ambition leads the affect of life such as the feeling of Id, Ego and Superego to achieve a dream.